Single-flap approach versus without concentrate growth factor in the treatment of periodontal supra-osseous defects: A randomized controlled clinical trial - Naglaa El-Wakeel; Lobna Mohamed Abd-elaziz (Elsevier, 2024)
Objectives: We aimed to compare treatment outcomes of periodontal supra-bony defects using single flap (SFA) plus concentrate growth factor versus SFA alone. Methods: 32 supra-bony periodontal defects were randomly assigned to test and control groups. Outcome variables were clinical attachment level (primary outcome). Probing pocket depths, gingival recessions, bone gain, post-surgical pain using visual analogue scale and wound healing index were recorded as secondary outcomes. Clinical and radiographic assessments were recorded at baseline and 6 months after treatment, whereas pain score and wound healing index were recorded within 10 days after surgery. Results: Test group showed a significant improvement in all tested parameters compared to control group (P-value ≤ 0.05). Better patient centered outcomes (wound healing and pain scores) were highly achieved in the test group compared to controls. Conclusion: The tested combined approach offers better periodontal and patient centered treatment outcomes in management of periodontal supra-bony defects.